An evaluation of the occupational stress among the employees - Siti Nur Fathihah, Azmi (2021)
This is an evaluation study on the occupational stress experienced among the employees in an insurance company. The employees were selected from the healthcare business unit which consists of four different departments namely medical claim operation, mediclinic, medicheck and cost containment. It has three main objectives. The first objective is to determine the level of occupational stress experienced by the employees. The second objective is to determine the factors (external stressors) that caused occupational stress among the employees. The third objective is to determine if demographic variables such as gender, marital status, age groups, position, education level, length of service and department have an impact on stress level. The finding of this study showed that generally the employees were experiencing low occupational stress level. The most common factors that caused occupational stress among the employees are work overload, time management and work condition. In term of demographic variables, the finding showed that employees in medical claim operation department were experiencing higher occupational stress level compared to other departments. The result proved that both hypotheses are accepted. There is relationship between external stressors variables namely work overload, inadequacy and reward system with occupational stress level and there is relationship between demographic variables namely department with occupational stress level. This finding implied that employees were able to cope well with the demand and challenges of the working environment as they were experiencing low occupational stress level. Nevertheless, company should maintain this by helping its employees to achieve mental, emotion and physical preparedness to cope with occupational stress effectively